1–D Framework l-arginine zinc(II) units bridged by oxalate: synthesis, structure, properties, and theoretical studies. Issue 5 (3rd March 2016) - Wojciechowska, Agnieszka; Kochel, Andrzej; Zierkiewicz, Wiktor
Abstract: We synthesized al -arginine containing Zn 2+ complex and oxalate ions. {[Zn2 (l -Arg)2 (ox)2 ]·8H2 O}n (1 ) (l -Arg  =l -arginine, ox  =  oxalate) crystallize in the monoclinic space group P21 with a   =  8.979(2), b   =  9.840(2) (Å), c   =  18.509(3) (Å), β   =  95.58(3) (Å), V  =  1627.6(6) Å 3, and Z  =  2. The zinc centers are six-coordinate via onel -arginine zwitterion and two bridging oxalates. The binuclear [Zn2 (l -Arg)2 (ox)2 ] units are linked via oxalate and form 1-D "stair-like" linear chains. The complex was characterized using FT-IR, FT-Raman, UV–vis spectroscopy, and thermal analysis techniques, as well as DFT methods. Electronic bands above 31, 000 cm −1 originate in 1, 3 A u ( n → π *) transitions within oxalate ions. Theoretical studies were performed for the model compound {[Zn(l -Arg)(Hox)2 ]·4H2 O} using the fragment of the crystallographic structure of1 . The interaction energy (ΔE) values forl -arginine and two oxalate ions are comparable at -145 kcal mol −1 . Natural bond orbital (NBO) analysis of the electronic structure and bonding is also discussed. Abstract :